Noções de verdade na estética arquitetônica: o caso de José Marianno Filho e o neocolonial brasileiro - Onofre, Carlos Eduardo Lins (2022)
Relations between truth and beauty have been discussed in the aesthetic field since antiquity. In architecture, the dialogue between these two dimensions is marked by different approaches, which can be emphasized in their material or intangible aspects. The context of neocolonial architecture in Brazil is fertile for deepening these issues, because, as a movement, it was strongly based on ideas and concerns about national identity, with critic José Marianno Filho as one of the most prominent figures in the elaboration and circulation of its discourse, especially between the 1920s and 1930s. The objective of this study is to discuss, through Marianno Filho's discourse on Brazilian cultural and artistic issues, within the neocolonial movement’s framework, how notions of truth can be elaborated in forming aesthetic judgments about architecture. A sample of texts authored by Marianno Filho published in Brazilian periodicals from the beginning of the 20th century was analyzed, which corroborated the hypothesis that notions of truth and authenticity take a fundamental position in arguments brought by the critic in his discourse on the neocolonial movement as a means to achieve a purposefully Brazilian architectural practice; these arguments repeat preexisting patterns from the general history of aesthetics, and privilege intangible dimensions of architecture.